Implementasi Pemasaran Produk Berbasis Digital Pada Media Sosial - Safitri, Reni Silvia Yuli (Business Management, 2025)
Digital-Based Product Marketing on Social Media is one of the steps taken to reach a broad target market. This study aims to determine the marketing process or actions taken by trading businesses in marketing their products on social media, this type of research is qualitative, the study was conducted in Teniga Village, North Lombok, the data collection technique was through interviews. The results of this study indicate that by carrying out product marketing actions or processes on social media makes it easier for business actors to market their products easily and with a broad target market, so that with social media business actors can improve the standard of quality of life, close the potential digital divide and of course improve the economy in the environment in Teniga Village.